Does vitamin E improve the smokers' salivary antioxidant status? - Mostafa Rezaei; seyed mohammad Mazloomi; Fatemeh Mohammadi; Maryam Shahrokhi sardo (Shiraz University of Medical Sciences, 2021)
Background: Vitamin E is known as a preventive or therapeutic antioxidant that improves the total antioxidant capacity (TAC) of saliva in individuals at risk of different oral cavity oxidative stresses. This study aimed to compare the effect of this vitamin on the salivary TAC between smokers and non-smokers. Materials and Methods: In this single-blind crossover clinical trial, non-stimulated saliva samples were collected from smoker and nonsmoker participants (n=60 per group) at three stages (baseline and after the two interventional phases). They were divided into subgroups to receive daily vitamin E (200 IU) and placebo for three weeks alternatively in the first or second phase. The salivary TAC was measured via fluorescence recovery after photobleaching method. The TAC changes were calculated in each phase. Data were analyzed by using SPSS software through repeated measures ANOVA, independent sample t-test, and covariate test. Results: The mean changes of TAC of smokers first receiving vitamin E and then placebo were 0.06±0.091 (U/mL) and 025.0±0.089 (U/mL), respectively (P=0.017). The non-smokers' mean TAC changes were 0.059±0.13 versus 0.053±0.129, respectively, after taking vitamin E and placebo; being statistically insignificant (P=0.791). Conclusion: Accordingly, vitamin E improved the salivary TAC in both non-smokers and smokers.